2010
DOI: 10.1016/j.enpol.2010.05.010
|View full text |Cite
|
Sign up to set email alerts
|

The taxation of UK oil and gas production: Why the windfalls got away

Abstract: Starting with evidence that United Kingdom Continental Shelf oil and gas companies have benefitted very disproportionately from the recent period of very high oil prices, this paper traces the history of this weakness in the UK's petroleum fiscal regime.Evidence is provided that the progressive relaxations in the UK's petroleum fiscal regime in 1983, 1987-88 and 1993 were: largely unnecessary to stimulate the development of new, smaller, 'marginal' fields; misguided in their assumption that such fields were m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…Our assessment of the effectiveness of resource taxation in the UK is relatively positive (in contrast to e.g. Abdo, 2010): on average over 65% of resource rent and 82% of resource depletion values were captured by taxes and royalties over 1975 to 2018. That said, our findings on the sustainability of the economy are less encouraging -for the same period we calculate depletion-adjusted net national saving for the UK, and conclude that on average this measure is less than 5% of GDP and it approaches 0 or is negative in some years.…”
Section: Introductionmentioning
confidence: 68%
See 1 more Smart Citation
“…Our assessment of the effectiveness of resource taxation in the UK is relatively positive (in contrast to e.g. Abdo, 2010): on average over 65% of resource rent and 82% of resource depletion values were captured by taxes and royalties over 1975 to 2018. That said, our findings on the sustainability of the economy are less encouraging -for the same period we calculate depletion-adjusted net national saving for the UK, and conclude that on average this measure is less than 5% of GDP and it approaches 0 or is negative in some years.…”
Section: Introductionmentioning
confidence: 68%
“…These charges themselves have undergone a number of revisions over the years, and PRT does not apply to fields developed after March 1993. 13 A number of other taxes have applied at earlier stages of the period we examine (Abdo, 2010;Nakhle, 2008). A 'Royalty' amounting to a charge on the gross value of oil and gas (less allowable deductions) produced applied to fields licenced before 1982 only and was discontinued altogether by 2002.…”
Section: Accounting For Government Resource Revenuesmentioning
confidence: 99%
“…The Government loosened the taxation burden on oil and gas companies in order to attract more oil and gas investment and hence, in the long term, collect more revenues. Previous studies have however shown that the Government was not successful in meeting these objectives (Abdo, 2010a;Rutledge and Wright, 2010). By intervening in the oil business, disposing the BNOC of, and relaxing the UK petroleum fiscal regime over the period 1983-2000, the Government was attempting to implement a non-proprietorial regime, but this attempt did not result in the expected win-win situation for the UK Government and the oil and gas industry.…”
Section: Analysis and Discussionmentioning
confidence: 99%
“…In other words, production in 1999 was 38% greater than it was in 1986, but revenues were 46% less in money-of-the-day (considerably less in real terms) even though the oil price was higher. Thus, the UK Government and UK citizens forfeited significant windfalls, without a commensurate response from companies in terms of increased investment, particularly as a result of the adoption of a non-proprietorial regime during that period (Abdo, 2010a).…”
Section: Analysis and Discussionmentioning
confidence: 99%
“…Other studies have investigated the effect of tax relaxation and introduction of new allowances on investment climate. Abdo (2010), in his United Kingdom (UK) study, examined the effect of the 1983,1987,1988 and 1993 fiscal regimes on companies' revenue. His result showed that relaxation of petroleum tax had different effects on investments in the United Kingdom Continental Shelves (UKCS), with each relaxation leading to Oil Company cash flow increase.…”
Section: Developed Countriesmentioning
confidence: 99%